The effectiveness of puppet theater performances in developing some educational values in kindergartens - Muibad Khalaf Rashid ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2021)
Educational values ​​constitute one of the foundations of the child’s educational process in developing children’s tastes through the presentations that carry in their subjects moral and educational implications that were deliberately worked on by those in charge of the puppet theater. It affects the child’s personality, so we have to present a set of educational, moral, educational and psychological values ​​in a theatrical way in how to develop the child’s personality through animated characters. Educational topics that correct the course of some undesirable educational values